Pengaruh Work from Home dan Family Supportive Supervisor Behaviors Terhadap Work-Life Balance dan Job Performance pada Karyawan Perusahaan Ritel di Jakarta Utara - Shafika Desty Ramadhanty; Netania Emilisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to determine the effect of Work from Home and Family Supportive Supervisor Behaviors on Work-Life Balance and Job Performance in Retail Companies in North Jakarta. This research was conducted using quantitative methods with Structural Equation Model (SEM) analysis. This study produced several findings, firstly, Work from Home has a negative influence on Work-Life Balance. Second, Work from Home has a positive influence on Job Performance. Third, Family Supportive Supervisor Behaviors has a negative influence on Work-Life Balance. Fourth, Family Supportive Supervisor Behaviors has a positive influence on Job Performance. Fifth, Work-Life Balance has a negative influence on Job Performance. This research is expected to provide benefits and insights about the importance of optimally and effectively managing human resources and the importance of the role of Family Supportive Supervisor Behaviors during Work From Home during the COVID-19 pandemic so as not to disrupt employee Work-